Evaluation of the effectiveness of pharmacotherapy for brain and heart diseases by monitoring the effects of drugs - Valeriya I. Kharina; Tatiyana A. Berezhnova (Belgorod National Research University, 2020)
Introduction: The study aims at analyzing the possibility of using a method of monitoring the action of drugs in real-time to assess the effectiveness of pharmacotherapy for brain and heart lesions. Materials and methods: To assess the effect of drugs in the experiment and in the clinic, the temperature difference between the biologically active point and the intact skin zone was recorded every second for 2 minutes. The work involved experimental and clinical parts. The experimental study was performed on 81 rabbits. In the experiment, the effect of Meldonium was evaluated when treating doxorubicin cardiomyopathy and the effect of Cortexin - when treating experimental brain ischemia. The clinical testing of the method involved 10 healthy volunteers and 20 patients of both sexes, diagnosed with acute cerebrovascular events of the ischemic-stroke type. Results and discussions: An increase of some indicators of differential thermometry of the biologically active point by 60% or more on the 7th day of the treatment concerning the values obtained before the treatment is indicative of a high probability of pronounced positive dynamics in the treatment of doxorubicin cardiomyopathy. If on the 7th day of the treatment, some indicators of differential thermometry of biologically active point С7 to exceed by 20% or more the similar indicators before the treatment, a high probability of pronounced positive dynamics in the treatment of ischemic stroke can be inferred. Conclusion: A safe, non-invasive method for monitoring the effects of drugs in real-time, which does not require any special training of a doctor, has been developed.